Implementation results of the project “The practical-experimental training in the natural sciences” - Yera Quintana, Andrés Israel (2018)
The article presents the results on the implementation of the project "The practical-experimental training in the natural sciences", in the teaching-learning process of the pre-university students of Ciego de Ávila municipality and in the degree in education in these specialties. Specifically, the theoretical conception assumed on the practical-experimental training (FPE) and the methodology to contribute to the said training were introduced in practice. As a mixed-case study, eight indicators were evaluated in four categories. The evaluations were carried out at the initial, two at the intermediate and final moments on the implementation of the project, based on the integrated analysis of the information obtained by the application of the designed instruments and according to the established criteria. An intentional sampling was carried out which included 294 participants, belonging to the five determined units of study. Progress was observed in all the indicators evaluated and notable among them those referring to the levels of socialization and application of the project results. The intermediate measurements allowed the improvement and adjustment of the implementation actions and favored a more effective and pertinent final finding. In general, progress was made in the quality of theoretical-practical work and seminars; the results of the evaluation of the learning process and the preparation of the subjects. Likewise, the satisfaction of students, teachers, technicians and educational managers regarding the improvement on the performance of their functions is noticed.